Prevalence of Myofascial Trigger Points in Patients with Radiating and Non-Radiating Low Back Pain: A Systematic Review - Germán Monclús-Díez; María José Díaz-Arribas; César Fernández-de-las-Peñas; Dariusz Kosson; Marcin Kołacz; Mateusz D. Kobylarz; Sandra Sánchez-Jorge; Juan Antonio Valera-Calero (Biomedicines)
Background/Objectives: Muscle tissues are a common source of symptoms related to low back pain (LBP), with myofascial trigger points (MTrPs) being a significant contributor. Since previous meta-analyses support interventions targeting MTrPs for reducing pain and improving functional disability in patients with LBP, this review aimed to synthesize current knowledge on the prevalence of MTrPs in LBP patients. Methods: To conduct this systematic review, data were collected from PubMed, Cochrane, and Web of Science. Published articles at any time up to February 2025 that comprised descriptive, observational, or experimental studies in English/Spanish language reporting the prevalence of active or latent MTrPs in patients with LBP were eligible. After assessing the methodological quality, a structured and qualitative synthesis was conducted using a standardized form that captured participant characteristics, evaluated muscles, the number or percentage of active and latent MTrPs in each group, clinical features, summarized results, and conclusions. Results: Nine articles with acceptable methodological quality were included. The prevalence of active MTrPs in patients with LBP was quadratus lumborum (ranging from 30% to 55%), gluteus medius (from 34% to 45%), piriformis (42%), psoas (from 5% to 10%), and lumbar iliocostalis (from 33% to 38%). Latent MTrPs were most common in the gluteus medius (74%) and quadratus lumborum (14–17%), with the piriformis, psoas, and lumbar iliocostalis also affected. Conclusions: Active and latent MTrPs are common in muscles such as the quadratus lumborum, gluteus medius, and iliocostalis in individuals with LBP, with prevalence varying by pain chronicity and etiology. MTrPs in the gluteal region are more frequent in lumbosacral radiculopathy, suggesting a neurogenic-like component. Since the subjectivity of manual palpation and study heterogeneity limit generalizability of the results, future research should standardize diagnostic criteria of MTrPs to ensure the consistency of results.